Impact of severe plastic deformation on kinetics and thermodynamics of hydrogen storage in magnesium and its alloys. (20th May 2023) - Edalati, Kaveh; Akiba, Etsuo; Botta, Walter J.; Estrin, Yuri; Floriano, Ricardo; Fruchart, Daniel; Grosdidier, Thierry; Horita, Zenji; Huot, Jacques; Li, Hai-Wen; Lin, Huai-Jun; Révész, Ádám; et al.
Highlights: Severe plastic deformation (SPD) effect on hydrogen storage in magnesium is reviewed. Mg-based hydrogen storage materials suffer from kinetic and thermodynamic drawbacks. SPD improves the kinetics, activation, and air resistance of Mg by lattice defect generation. SPD synthesizes alloys with thermodynamics suitable for low-temperature hydrogen storage. Abstract: Magnesium and its alloys are the most investigated materials for solid-state hydrogen storage in the form of metal hydrides, but there are still unresolved problems with the kinetics and thermodynamics of hydrogenation and dehydrogenation of this group of materials. Severe plastic deformation (SPD) methods, such as equal-channel angular pressing (ECAP), high-pressure torsion (HPT), intensive rolling, and fast forging, have been widely used to enhance the activation, air resistance, and hydrogenation/dehydrogenation kinetics of Mg-based hydrogen storage materials by introducing ultrafine/nanoscale grains and crystal lattice defects. These severely deformed materials, particularly in the presence of alloying additives or second-phase nanoparticles, can show not only fast hydrogen absorption/desorption kinetics but also good cycling stability. It was shown that some materials that are apparently inert to hydrogen can absorb hydrogen after SPD processing. Moreover, the SPD methods were effectively used for hydrogen binding-energy engineering and synthesizing new magnesium alloys with low thermodynamic stability for reversible low/room-temperature hydrogen storage, such as nanoglasses, high-entropy alloys, and metastable phases including the high-pressure γ-MgH2 polymorph. This work reviews recent advances in the development of Mg-based hydrogen storage materials by SPD processing and discusses their potential in future applications. Graphical abstract: Image, graphical abstract